(untitled) (Journal of Innovation and Technology Polbeng Series on Informatics (INOVTEK Polbeng - Seri Informatika), 2026)
The Loan Origination System (LOS) has become a key infrastructure in Indonesia’s digital mortgage lending ecosystem, where technological innovation increasingly intersects with regulatory governance. This study examines LOS through an integrated perspective that bridges information systems architecture and legal-regulatory frameworks. Using a qualitative normative-analytical approach grounded in systematic document analysis (2021–2026) and thematic synthesis, the research identifies a triple-layer compliance gap: a regulatory gap in technical specification, an implementation gap between regulatory intent and system design, and a legal defensibility gap concerning evidentiary robustness. The study proposes a conceptual legal-by-design framework integrating technical security, regulatory alignment, and evidentiary considerations within a unified architectural model. Rather than offering a validated industry standard, the framework serves as an analytical proposal to inform future empirical research and institutional system development.